Appropriate Climate Change Solutions: Towards Sustainable Bioenergy Agro-production in Africa for Energy Equality and Poverty Alleviation - Duvenage, Ian; Taplin, Ros; Stringer, Lindsay C. (The international journal of climate change: Impacts and responses, 2011)
Limited energy access within developing nations particularly in Africa is a primary reason for poverty. Biofuel production has been advocated by many experts as a solution to meeting the energy needs of African countries while reducing greenhouse gas (GHG) emissions. Others argue that biofuel production will compete with land needed for food production. However it appears many African countries have available land beyond food needs, hence biofuel production may be an option for poor farmers to gain skills, create economic diversification and provide affordable energy without environmental degradation. This paper reviews the situation in Africa with regard to biofuels and sustainability. It argues that biofuels produced within a sustainable production framework, could improve rural infrastructure, job opportunities, education and health. A new bioenergy production framework is proposed which includes a novel element: agro-management alongside other sustainability elements. The framework is designed as a prerequisite for bioenergy project proposals in Africa. Addressing climate change by advancing biofuels, taking into account equality, land rights and environmental considerations, may be achieved in many African countries, with the implementation of such a framework.
openalex: W1592901422 mag: 1592901422
Keywords: openalex:import